“Modelo de gestión y disposición final de elementos de bioprotección como desecho sólido peligroso en la ciudad de Ambato, provincia de Tungurahua” - Benítez Herrera, Álvaro Xavier (2021)
The present research work was carried out with the purpose of sampling and characterizing the solid hazardous waste generated by the population of the city of Ambato, for the use of bio protection elements for COVID-19, and to be able to elaborate the model of Biosanitary Solid Hazardous Waste Management of the city of Ambato, province of Tungurahua. The characterization and determination of the volume of solid hazardous biosanitary waste generated by the population of the city of Ambato was carried out in the urban parishes of the city of Ambato, during one week; at the established points which were the 9 urban parishes that make up the city such as: La Merced, La Matriz, La Peninsula, Atocha-Ficoa, Pishilata, Huachi Chico, Huachi-Loreto, San Francisco, and Celiano Monge, the weighing was executed with an electronic scale, where it was determined that the total bio-sanitary hazardous solid waste collected was 1074 g/day, in the 9 urban parishes, which means that an average value of 153.43 g/day is generated, for each urban parish of the city of Ambato. With the results obtained from the characterization and determination of the volume of biohazardous solid waste generated by the population of the city of Ambato, the following values were obtained in each parish; La Merced with a value of 377 g/day; La Matriz with a value of 132 g/day; La Peninsula with a value of 234 g/day; Atocha-Ficoa with a value of 207 g/day; Pishilata with a value of 108 g/day; Huachi-Chico with a value of 240 g/day; Huachi-Loreto with a value of 354 g/day; San Francisco with a value of 213 g/day; and Celiano Monge with a value of 159 g/day determining that the type of bio-protection element most discarded by the population is the surgical mask since due to its cost it has generated greater acceptance in the population as opposed to the other types of bio-protection element; according to these results the Biosanitary Hazardous Solid Waste Management model established in the International Standard (ISO) 14001 was elaborated: 2015; also contemplating the current environmental regulations of Ecuador applicable to the handling and proper management of solid hazardous biosanitary waste for its 1 xiii future application and implementation by the entity in charge of regulating the management of solid hazardous biosanitary waste generated in Ambato city .